Why cutting is easier than tearing elastomers - Donghao Zhao; Alex Cartier; Tetsuharu Narita; Frederic Lechenault; Costantino Creton; Matteo Ciccotti (Nature Communications)
Abstract Tearing tough soft solids such as rubbers, leather or meat is much harder than cutting them with a sharp blade. To understand why, we use samples labeled with mechanically sensitive fluorophores to investigate cutting and fracture behavior in PDMS elastomers and quantify the extent of bond scission resulting from cutting pre-stretched samples. Our findings reveal that stretch-induced cracks produce significant deformation, bond scission and blunting near the crack tip, requiring more energy to propagate. In contrast, using blades reduces the amount of stretching and blunting required for crack propagation, resulting in a lower fracture energy. The measured linear correlation between fracture energy and the areal density of broken chains clarifies the relationship between pre-stretching, blunting, and molecular damage. These multi-scale insights demonstrate the key differences between fracture and cutting mechanics of soft materials, allowing to optimize engineering applications, such as rubber and food processing, energy-efficient recycling, biomedical and surgical devices, protective equipment and sports gear.